2003
DOI: 10.1002/joc.915
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the climatological growing season (1951–2000) in Germany compared with other countries

Abstract: We analyse how variations in the climatological growing season, defined by single-value thresholds of daily minimum and mean air temperature, mirror recent changes in plant phenological phases. In Germany 41 climate stations), the dates of last spring frost T min < 0°C (<−3°C and <−5°C) advance by 0.24 (0.23 and 0.32) days per year on average, and the first day when the daily mean temperature constantly exceeds 5°C (7°C and 10°C) advances by 0.13 (0.21 and 0.09) days per year. The respective autumn dates are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
91
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(105 citation statements)
references
References 37 publications
(19 reference statements)
12
91
0
2
Order By: Relevance
“…The u* threshold for determining the low turbulence fluxes was calculated following Reichstein et al (2005) for two layer fluxes based on u*, CO 2 fluxes, and T a . Following Menzel et al (2003), we determined the start and the end of growing-season based on daily T a . Negative CO 2 fluxes at nighttime (when the solar elevation angle was lower than 0 • ) and at non-growing season were then also removed.…”
Section: Data Preparingmentioning
confidence: 99%
“…The u* threshold for determining the low turbulence fluxes was calculated following Reichstein et al (2005) for two layer fluxes based on u*, CO 2 fluxes, and T a . Following Menzel et al (2003), we determined the start and the end of growing-season based on daily T a . Negative CO 2 fluxes at nighttime (when the solar elevation angle was lower than 0 • ) and at non-growing season were then also removed.…”
Section: Data Preparingmentioning
confidence: 99%
“…Menzel et al (2003) analysed 41 stations in Germany in the period 1951-2000, where the GS was defined by single-value thresholds of daily minimum and mean air temperatures, and during the 50-year period they found a lengthening of the GS by 5.5 to 24.5 days 41 depending on the index used. Similar to China, they found the greatest change in the frost-free period, and related that to a stronger increase in daily minimum rather than maximum temperatures.…”
Section: Gs Changes In China 1951-2007mentioning
confidence: 99%
“…This focus on the GS start in phenological studies is due to (1) the largest changes having been noticed in spring and (2) the relatively large uncertainty in timing the end of the GS. The reported increases in GS length (GSL) are in a range of 1-3 weeks in the last few decades (Skaggs and Baker, 1985;Carter, 1998;Hasenauer et al, 1999;Robeson, 2002;Schwartz and Chen, 2002;Menzel et al, 2003;Linderholm et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Menzel et al (2003) used data from 41 meteorological stations across Germany (from 1951 through 2000) to investigate soil frost dynamics. Their results showed that the freeze-free period was extended with increasing air temperature.…”
Section: Introductionmentioning
confidence: 99%